A Pendampingan Peningkatan Pemberdayaan Masyarakat Kelurahan Prambangan Kabupaten Gresik Melalui Pelatihan Literasi Keuangan Di Masa Pandemi Covid-19 - Anita Akhirruddin (Jurnal Pengabdian Manajemen, 2022)
The Corona (Covid-19) outbreak that emerged in 2020 in Indonesia. The world economy has been is shambles due to the weakening of world economic growth, including Indonesia. This has resulted in many households experiencing economic diffuculties as a result of declining incomes due to the declining purchasing power of the people. This decline in family makes housewives as a Financial Planner to be wise in managing household finances during this pandemic. For this reason, in the communty service, it is necessary to provide education regarding good financial planning for business continuity and family finances. After trainning and mentoring, there was an increase from 36 npercent to 80 percent in the form of the financial recording process using available applications, how to get a loan and what are the conditions. Assitance related to the use of e-commerce platforms that can reach a wider range of consumers. This assistance also explains how our products can be accepted by consumers, especially processed food, for that it is necessary to create an SPP-IRT that gives a sense of trust because it already has a distribution permit that already meets foot safety standards.